2006
DOI: 10.1590/s1413-41522006000100005
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho da filtração lenta em areia submetida a cargas de pico de oocistos de Cryptosporidium sp, bactérias e sólidos: uma avaliação em instalação piloto

Abstract: Nos EUA, Cryptosporidium parvum tem atraído considerável atenção devido aos surtos de criptosporidiose atribuídos aos suprimentos de água contaminados com oocistos. Devido à magnitude sem precedentes do surto ocorrido em Milwaukee, em abril de 1993, houve ampla divulgação e muitos estudos se iniciaram. Informações coletadas durante este e em outros surtos posteriores vêm sendo avaliadas, com o objetivo de se definirem medidas efetivas que possam reduzir o risco de futuros surtos de doenças veiculadas pela água… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
2
0
3
Order By: Relevance
“…In addition, seasonal monitoring aims to characterize the aquatic environment, since bacteria in the coliform group are not good indicators of the prevalence of protozoa (HORMAN et al, 2004) and due to the underestimation of risk of infection caused by punctual samples (HELLER et al, 2006), as performed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, seasonal monitoring aims to characterize the aquatic environment, since bacteria in the coliform group are not good indicators of the prevalence of protozoa (HORMAN et al, 2004) and due to the underestimation of risk of infection caused by punctual samples (HELLER et al, 2006), as performed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…24,[30][31][32] In Brazil, several studies have reported Cryptosporidium oocysts in raw or treated sewage and bottled mineral water by using immunomagnetic separation or Percoll or sucrose gradients, followed by immunofluorescence, phase contrast microscopy, or epifluorescence. [13][14][15]33 Hachich and others 11 studied different hydrographic basins containing water for human consumption in the State of São Paulo by using the 1623 USEPA method. They reported prevalences of 2.5% for Cryptosporidium oocysts and 27% for Giardia cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Nos Estados Unidos, Europa e mesmo no Brasil, vários trabalhos apontam a capacidade da filtração lenta em remover protozoários, vírus, bactérias e turbidez (TIMMS et al, 1993apud. PROSAB, 2006DULLEMONT et al, 2006;HELLER et al 2006;SCHULER, GHOSH e GOPALAN, 1991;JENKINS, TIWARI e DARBY, 2011).…”
Section: Introdução E Objetivosunclassified